SIFAT FISIS DAN KEKERASAN PAPAN BLOK DARI BATANG KELAPA SAWIT DAN FINIR JENIS KAYU CEPAT TUMBUH - Mangurai, Silvia Uthari Nuzaverra Mayang; Massijaya, Muh Yusram; Hadi, Yusuf Sudo; Hermawan, Dede; Abdillah, Imam Busyra; Munadian, Munadian (JURNAL HUTAN LESTARI, 2024)
The oil palm trunk and fast-growing species was the potential as raw materials for blockboard. The quality of composite board can be reflected by the value of physical and mechanical properties that influenced by the characteristics of veneer, board core and type of adhesive and the method of manufacturing. The aim of this research was to produce block boards from oil palm trunk waste and sengon (Paraserianthes falcataria (L.) Nielsen), manii (Maesopsis eminii Engl.), mangium (Acacia mangium Willd.) veneers as surface layers. The size of the blockboards was 35 x 35 x 2.4 cm3. The adhesives used were phenol formaldehyde (PF) and urea formaldehyde (UF) with glue spread of 200 g ·m-2. The blockboards were made with a pressure of 15 kg ·cm-2 for 10 minutes at 130 oC for PF and 110 oC for UF. The physical and mechanical properties of the boards were tested based on SNI 01-7201, JAS 232ï€ 2003 and JIS A 5908-2003 standard. The research results show that the wood veneer species and adhesive types can improved the physical properties and hardness of block board with oil palm trunk core. Moisture content value of the boards had less than 10% and the thickness sweeling had less than 12%. Thickness swelling and delamination were influenced by adhesive types. Block board with PF adhesive have a lower delamination value than bloc board with UF adhesive so it can be used for exterior purposes. The hardness value blockboard fulfil BS standard and recommended for flooring applications.Keywords: adhesives types, blockboard, fast-growing species, oil palm trunk, physical properties and hardnessAbstrakLimbah batang kelapa sawit dan jenis kayu cepat tumbuh mempunyai potensi sebagai bahan baku papan blok. Kualitas papan komposit dapat terlihat dari sifat fisis dan mekanis yang dipengaruhi oleh karakteristik finir, bagian inti papan, jenis perekat, dan metode pembuatannya. Tujuan penelitian ini adalah untuk menentukan sifat fisis dan kekerasan papan blok dari limbah batang kelapa sawit dan sengon, manii, dan mangium finir sebagai lapisan permukaan. Papan blok berukuran 35 x 35 x 2,4 cm3. Perekat yang digunakan adalah fenol formaldehida (PF) dan urea formaldehida (UF) dengan berat labur sebesar 200 g ·m-2. Papan blok dibuar dengan tekanan 15 kg ·cm-2 selama 10 minutes pada suhu 130 oC untuk perekat PF and 110 oC untuk perekat UF. Sifat fisis dan kekerasan diuji berdasarkan standar SNI 01-7201, JAS 232ï€ 2003, dan JIS A 5908-2003. Hasil penelitian menunjukkan bahwa jenis kayu dan jenis perekat dapat membantu meningkatkan sifat fisis dan kekerasan papan blok dengan inti batang kelapa sawit. Nilai kadar air papan blok dibawah 10% dan pengembangan tebal dibawah 12%. Papan blok dengan perekat PF mempunyai nilai delaminasi lebih kecil dibandingkan papan blok dengan perekat UF dan dapat digunakan sebagai keperluan eksterior. Nilai kekerasan papan blok BKS telah memenuhi Standar British yang direkomendasikan untuk aplikasi lantai.Kata kunci: batang kelapa sawit, jenis kayu cepat tumbuh, jenis perekat, papan blok, sifat fisis dan kekerasan